PENGARUH KETIDAKPASTIAN LINGKUNGAN DAN DESENTRALIASASI TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN (Studi pada PT. Industri Telekomunikasi Indonesia Bandung) - Ajeng Purwanti (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
Environmental uncertainty and decentralization are popular and complex concepts that are identified as factors that can affect the quality of management accounting information systems. The phenomenon that occurs in Indonesia is the quality of accounting information system that has not been perfect. Similarly, environmental uncertainty and decentralization have not shown the ideal conditions. The purpose of this study is to achieve the truth through testing (confirmation) the influence of environmental uncertainty and decentralization on the quality of management accounting information system at PT. Industri Telekomunikasi Indonesia (Persero) Bandung. The data used is obtained through survey by distributing questionnaires at PT. Industri Telekomunikasi Indonesia (Persero) Bandung, processed statistically with the help of Smart-PLS software. The method used in this research is descriptive analysis method verifikatif. The results showed that: (1) environmental uncertainty affecting the quality of management accounting information system and (2) decentralization affect the quality of management accounting information system.